Pengaruh Kompensasi dan Beban Kerja terhadap Produktivitas Kerja Karyawan pada PT Intigarmindo Persada Jakarta Pusat - Tahani Luthfiana; Eigis Yani Pramularso (Indo Publishing, 2026)
This study was motivated by the importance of employee work productivity in supporting the achievement of production targets in the garment industry. PT Intigarmindo Persada, a company engaged in the garment manufacturing industry, requires high employee productivity to achieve its production targets and maintain product quality. Based on the observations, some employees perceived that the compensation they received was not commensurate with their job responsibilities and that their workload was relatively high. These conditions were considered to affect employee work productivity. This study employed a quantitative research method. Data were collected through observation, questionnaires, and literature review. The population consisted of 50 employees in the Quality Control Division, all of whom were selected as the sample using the saturated sampling technique. The data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination with the assistance of IBM SPSS. The results showed that compensation had a positive and significant effect on employee work productivity. Workload also had a positive and significant effect on employee work productivity. Simultaneously, compensation and workload had a positive and significant effect on employee work productivity, with a coefficient of determination of 47.7%, while the remaining 52.3% was influenced by other factors that were not examined in this study.